Teamwork in Airway Surgery - Elliott, Martin J.; Roebuck, Derek; Muthialu, Nagarajan; Hewitt, Richard; Wallis, Colin; DeCoppi, Paolo; Macintyre, Denise; McLaren, Clare Ann (Frontiers in Pediatrics, 2021)
Previously Submitted